EFFECTIVE EDUCATION ABOUT HEALING TO MANAGE STRESS PENDIDIKAN KEFEKTIFAN TENTANG HEALING UNTUK MENANGANI STRES - Nur Amsyiah R Djunaidi; Frezy Paputungan; Ade Yul Pascasari (LPPM UNiversitas Bina Mandiri Gorontalo, 2023)
The emergence of this self-healing phenomenon attracted a lot of attention from generation Zduring the pandemic, starting in 2021 until now. According to (Madura, 2021) self-healing meansself-healing, in other words healing means